If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5y + 6z = 33 Solving 2x + 5y + 6z = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. 2x + 5y + -5y + 6z = 33 + -5y Combine like terms: 5y + -5y = 0 2x + 0 + 6z = 33 + -5y 2x + 6z = 33 + -5y Add '-6z' to each side of the equation. 2x + 6z + -6z = 33 + -5y + -6z Combine like terms: 6z + -6z = 0 2x + 0 = 33 + -5y + -6z 2x = 33 + -5y + -6z Divide each side by '2'. x = 16.5 + -2.5y + -3z Simplifying x = 16.5 + -2.5y + -3z
| -2.5c-1.7=-.5c+14.3 | | 3y+7=4y+2 | | 7bc= | | 7(2l+3)=35 | | 6x+3y+10x+15y=180 | | 8x(8x)-40x=0 | | 5m-3n-4= | | (X+20)+(x+10)+x=105 | | 6.8x-1.2=26.0 | | 6n+8m= | | (u+4)*8=40 | | 2x-12x+10=0 | | 8cos^2x-7cosx+1=0 | | 10x-2=3x+5 | | 8x(8x-40x)=0 | | x/2521 | | (q-3)*5=45 | | 2(2.1+.1y)=-8.7+.2y | | 24-4y=16 | | 7/8+x=21 | | 7x+6=2x+36 | | 2.6p-8.7p+4.7=93.96 | | x+3+2x=x+6 | | 21y-15= | | 0=x^2+82x+2320 | | 5(4s+6)=190 | | 10x-2=5x+23 | | 29.27=l^3 | | (X+20)+(x+10)+x= | | 6z-8-2+3=0 | | -4(1-7n)=-26 | | 9(1-9v)=477 |